Pengaruh Gaya Kepemimpinan dan Budaya Organisasi pada Kinerja Guru dengan Motivasi Sebagai Variabel Intervening - Aurelia Dewanggi H.P.; Hunik Sri Runing Sawitri (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2016)
Purpose of this study to analyze the effects of leadership style, organizational culture on motivation and performance of senior high school techers in Wonogiri. Job performance is very necessary for any profession. Job performance of teacher increasingly organizational performance so that purpose of company or organization can be reachable. Many factors which can increase job/activity such as leadership style, organizational culture, and motivation.How far leadership style and organizational culture influence to job performance is tested in this research, by insert motivation as intervening variables.Test utilized to analyze leadership style and organizational culture influence to job performance that is path analysis,R2test, as well as statistic T test, and direct and inderct effect. Research data obtained from questionary answer propagated to the teacher of senior high school in Wonogiri. Result of research analysis express that leadership style and organizational culture has positive influence and significant to teachers job performance. And Motivation proof to be intervening variabel in relationship beetwen leadership style and organizational culture to teachers job performance.